Consumer use intention of online financial products: the Yuebao example - Huosong Xia; Zhe Hou (Financial Innovation, 2016)
Drawing on a valence framework and innovation diffusion theory, this study examines Yuebao deployment to model consumers' intention to use financial products offered online. We collect data via an online survey among a young age bracket and use a VisualPLS graphic interface to test our model. The results indicate that first, compatibility and advantages in relative utility significantly enhance consumers' use intentions and that ease of use has an indirect influence. Second, the negative utility of perceived risk no longer significantly affects intention to use. This mainly lies in consumers' perceived risk focused on the security of online financial products, which has become a part of all online transactions. Third, trust indirectly affects intention to use by influencing utility.
Keywords: 650; Online financial products; Utility; Trust; Innovation diffusion theory; Use intention; Yuebao